HUBUNGAN POSTUR KERJA DENGAN KEJADIAN KELELAHAN OTOT PUNGGUNG PADA PEKERJA MEBEL BAGIAN PENGAMPLASAN DI PT. X JEPARA - Hanifah Ismiarni; Baju Widjasena; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Unproper, awkward and unusual postures will increase risk of injury to the musculoskeletal system. It was found that many workers in the sanding department of PT. X, Jepara work with awkward postures, such as bending, twisting, squat, etc, thus giving a heavy postural load to the back muscles. Therefore, a study was performed to correlation between work posture and back muscle fatigue on the sanding department of PT. X, Jepara. Number of samples used in this study were 58 respondents using proportional purposive sampling method with inclusion criteria of employees who are willing to become respondents, female and had no physical injuries. Data were collected using QEC (Quick Exposure Count) to assess posture and using back dynamometer for the back-muscle fatigue. Results show that workers tend to have high and very high work posture exposure (mean=71%, median=70%, mode=69%) and back muscles fatigue tend to be very high (mean= 48,8lbs, median= 50lbs, mode= 31lbs). Statistical tests were conducted to see the correlation between these two variables using correlate bivariate Product Moment Pearson test. Study shows that there is a correlation between work posture and back muscle fatigue (pvalue = 0.029). Researcher suggested that workers need to balance the work with stretching, in addition the company needs to support this by creating a supportive working system.